THE INFLUENCE OF RELIGIOSITY AND BELIEF ON INTEREST IN PAYING NON-CASH ZAKAT THROUGH THE DIGITAL ISLAMIC BANKING SYSTEM: A Study on Muslim Millennials in Bandar Lampung - Putri, Aprila Sari Ardini; Purnamasari, Femei; Nurmalia, Gustika (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
This study aims to analyze the influence of religiosity and trust on the interest in paying non-cash zakat through the digital Islamic banking system among the Muslim millennial generation in Bandar Lampung City. The background of the study is based on the rapid development of digital technology and the increasing trend of donations through digital channels, especially during and after the COVID-19 pandemic. In this context, religiosity and trust are assumed to be two main factors influencing an individual's decision to distribute non-cash zakat. This study uses a quantitative approach with a survey method through a questionnaire distributed to 96 respondents. Data analysis was conducted using multiple linear regression to test the relationship between the independent variables (religiosity and trust) and the dependent variable (interest in paying non-cash zakat). The results show that religiosity has no significant effect, while trust has a positive and significant influence on the interest in paying non-cash zakat through the digital Islamic banking platform. These findings provide important implications for zakat management institutions and Islamic financial institutions in developing more effective zakat digitalization strategies that are in line with the characteristics of the millennial generation.